Electrospun curcumin/polycaprolactone/copolymer F‐108 fibers as a new therapy for wound healing. Issue 9 (21st August 2019) - Thaiane da Silva, Thamara; Cesar, Gabriel Batista; Francisco, Carolina Pereira; Mossini, Guilherme Galerani; de Castro Hoshino, Lidiane Vizioli; Sato, Francielle; Radovanovic, Eduardo; da Silva Agostini, Deuber Lincon; Caetano, Wilker; Hernandes, Luzmarina; Matioli, Graciette
ABSTRACT: The application of fibers associated with drugs is a promising alternative to meet the clinical needs of tissue repair. Curcumin exhibits great cicatricial potential because it has numerous pharmacological properties. This research aimed to produce fibers of polycaprolactone and copolymer F‐108 associated with curcumin and to evaluate in vivo their action on the process of wound healing. The fibers were produced by electrospinning technique and characterized by scanning electron microscopy (SEM), X‐ray diffractometry (XRD), and fluorescence microscopy. They were applied in cutaneous wounds of rats for the analysis of photoacoustic permeation and histological study. The characterization showed that the electrospinning allowed the preparation of homogeneous material with curcumin. The fibers benefited healing of the wounds and allowed the permeation of curcumin at all stages. The use of PCL/F‐108 fibers allowed the elaboration of a new curcumin delivery system, improving its bioavailability and action in the healing of excisional wound. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48415. Abstract : Evaluation of PCL/F‐108‐Curcumin fibers in wound healing.